EFEKTIVITAS EKSTRAK BAWANG MERAH (Allium ascolanicum L.) DENGAN PERIODE PERENDAMAN TERHADAP INVIGORASI BENIH KEDELAI (Glycine max L.) - Widiatmanta, Jeka; Wibowo, Agung Setya (Universitas Islam Balitar, 2024)
This study was conducted to determine the effect of soaking soyabean seeds in shallot extract, a natural ZPT, on viability and seed growth. The research was conducted from August to October 2024 in the experimental garden of the Faculty of Agriculture, Barital Islamic University using a completely randomised design (CRD) with five treatments and four replications. The treatments were seed soaking in water for 1 hour and shallot extract for 2, 3, 4 and 5 hours. Parameters observed included growth vigour, growth rate, growth synchronisation, and vigour index. The results showed that soaking for 3 hours gave the best results on all variables.